GE_GERICHTE P/12012/2016 vom 15. Februar 2023 - GE Cour de justice (2023)
RETRAIT(VOIE DE DROIT);DÉFENSE D'OFFICE;FRAIS DE LA PROCÉDURE;INDEMNITÉ(EN GÉNÉRAL) | CPP.386.al2.leta; CPP.401.al3; CPP.428.al1; CPP.135; CPP.138